2015
DOI: 10.1093/eurpub/cku222
|View full text |Cite
|
Sign up to set email alerts
|

Measuring hospital efficiency—comparing four European countries

Abstract: Panel data are preferred over cross-section analysis because results are more robust. For all countries except Slovenia, beds and employees are relevant inputs for the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The following health economic factors, one output and six inputs, were based on previous studies, 3842 and were obtained from the China Health Statistics Yearbook. OE it is the number of outpatient and emergency room visits per 1000 personnel (output).…”
Section: Methodsmentioning
confidence: 99%
“…The following health economic factors, one output and six inputs, were based on previous studies, 3842 and were obtained from the China Health Statistics Yearbook. OE it is the number of outpatient and emergency room visits per 1000 personnel (output).…”
Section: Methodsmentioning
confidence: 99%
“…It was recommended that raising the allocation of funds for the health workforce can improve efficiency. Mateus, Joaquim, and Nunes (2015), Novignon and Lawanson (2014), and Adam (2012) assessed and compared hospital efficiency levels within and between countries using SFA with cross-section and panel data and OLS. The results revealed that in cross-sectional data SFA was not statistically different from OLS for one country while these were statistically different for other countries.…”
Section: Review Of Literature: Application Of Stochastic Frontier Analysis (Sfa)mentioning
confidence: 99%
“…The results revealed that in cross-sectional data SFA was not statistically different from OLS for one country while these were statistically different for other countries. As it gives robust results panel data were preferred over cross-section analysis (Mateus et al, 2015). Adam (2012) suggested that the differences in hospital costs were due to differences in country-specific productivity.…”
Section: Review Of Literature: Application Of Stochastic Frontier Analysis (Sfa)mentioning
confidence: 99%
“…Public health system efficiency and quality is challenged by factors including tightening budgets, growing demand, professional shortages, increasing disease burdens, increasing pressure on infrastructure, technological implications, changing service models and changing service accessibility (4) . An ongoing state of inefficiency amidst an environment of seemingly-constant reform is characteristic of the public health systems of many well-developed countries around the world (5,6) . Compounding this state is a common trend in rates of growth in health services demand in excess of funding growth rates, creating further pressure on already-burdened public health systems (7) .…”
Section: Introductionmentioning
confidence: 99%